Synthesis of novel high-entropy diborides with high-efficiency electromagnetic wave absorption and excellent thermal stability - Chencheng Liu; Qingyun Chen; Peng Sun; Xingye Wang; Shuyi Zeng; Qijie Chen; Tong Zhu; Yi Zhu; Wenlong Zhang; Hui Song; Yuezhong Wang; Kazuhito Nishimura; et al. (Journal of Advanced Ceramics, 2025)
Ceramic materials have obvious advantages in thermal stability, but impedance mismatch limits their ability to attenuate electromagnetic (EM) waves. Herein, a novel series of high-entropy (V0.2Nb0.2Zr0.2Ta0.2X0.2)B2 (X = Mo, Ti, and Hf) ceramics were successfully synthesized via ultrafast high-temperature sintering (UHS) apparatus based on joule heating. The results indicated that the effect of high-entropy component on the magnetic loss of the system was relatively small, but the effect on the dielectric loss was larger. Among them, the (V0.2Nb0.2Zr0.2Ta0.2Ti0.2)B2 (HEB-Ti) sample demonstrated superior absorbing properties due to relatively moderate dielectric loss and optimal EM impedance matching. Moreover, because of its relatively moderate attenuation constant, it could achieve the maximum penetration of the EM wave and the minimum reflection after absorbing wave. As a result, the minimum reflection loss (RLmin) was as low as −40.7 dB, and the effective absorption band covered the entire low-frequency range from 2 to 8 GHz. Its excellent absorption performance was mainly due to the synergistic effect of various dielectric attenuation mechanisms, including defect polarization, dipole polarization, and conduction loss. Furthermore, thermogravimetric (TG) analysis showed that the sample exhibited excellent thermal stability and could withstand temperatures up to 550 °C in air and 1000 °C in an argon gas environment. The relevant work could provide meaningful references for the design of new high-performance ceramic wave-absorbing materials.